Penggunaan Informasi Akuntansi dan Umur Usaha Mendorong Keberhasilan Usaha Mikro Kecil dan Menengah Batik di Kota Yogyakarta - David Rianto; Amir Hidayatulloh (Sains: Jurnal Manajemen dan Bisnis, 2020)
The purpose of the study was to analyze the effect of using accounting information and business age on business success. The population in this study is the MSMEs who are in the Special Region of Yogyakarta. The sample in this study in were batik MSMEs who were in the Special Region of Yogyakarta. The sampling technique in this study used purposive sampling with criteria of MSMEs who had recorded their business. The data collection of this study used a survey method which was carried out by distributing questionnaires directly to respondents who met the criteria. The respondents of this study were 40 respondents. Data analysis techniques in this study used multiple linear regression analysis with help of SPSS tools. This study found that the success of MSMEs was influenced by the use of accounting information and business age.